From Stefan Norblin to Mieczyslaw Berman. Some Remarks on the Covers of Books Published Under the Sign of Three Honeybees - Krzak-Weiss, Katarzyna (Porównania, 2025)
The subject of this article is the analysis of selected cover designs used in books published by Towarzystwo Wydawnicze “Rój” – one of the leading Polish publishing article presents an analysis of the works of four artists who cooperated most often with the company signing its publications with the sign of the three bees: Stefan Norblin, Tadeusz Gronowski, Henryk Nowina-Czerny and Mieczyslaw Berman, who enjoyed a well-deserved reputation at the time as some of the most interesting graphic designers. The multiplicity and diversity of the designs they produced proves that those in charge of “Rój” were well aware of the impact the cover could have on the public.